8 - Book Reviews: Struggle for the University A Review Article - Zeleza, Paul Tiyambe (Africa Development, 1997)
The African Experience with Higher Education, by J. F. Ade Ajayi, Lameck K. H. Goma, and G. Ampah Johnson, Accra, The Association of African Universities, 1996, p.xii+276; The African University and Its Mission, by Emanuel Ngara, Lesotho, The Institute of Southern African Studies, 1994, p.xviii+194; Towards a Commonwealth of Scholars: A New Vision for the Nineties, by Lalage Bown, ed., London, Commonwealth Secretariat, 1994, p.xii+245; and The State of Academic Freedom in Africa 1995, by CODESRIA, Dakar, CODESRIA, 1996, p.189.